The double-edged sword: financial source of household healthcare expenditure in Ghana - Henry Armah Tagoe (AOSIS, 2012)
In many regions, some of the most formidable enemies of health are joining forces with the allies of poverty to impose a double burden of disease, disability and premature death. This paper looks at the main financial sources households use to finance healthcare in Ghana. It examines the spatial and socio-economic dynamics and the challenges these pose to health and development. Analysis of the 2003 Ghana World Health Survey data indicates that approximately 41% of households depend on more than one financial source with 88% depending on household income to finance healthcare expenditure. The high dependency on household income will erode gains in the economic and health sector in the midst of the recent global economic recession. Comprehensive national health insurance programs that cover emerging disease conditions will mitigate the double burden of disease on households in emerging economies.